16 Quality-adjusted (QA) progression-free survival analyses of veliparib + carboplatin/paclitaxel (CP) vs CP alone in patients with newly diagnosed ovarian cancer. (13th November 2020) - Alvarez Secord, A; Bookman, M; Coleman, R; Dinh, M; Khandelwal, N; Benjamin, K; Kamalakar, R; Sullivan, D; Cella, D
Abstract : Objective: Veliparib, a poly (ADP-ribose) polymerase inhibitor, was evaluated in a Phase 3 trial (VELIA, NCT02470585 ) among patients with newly diagnosed stage III/IV high-grade serous epithelial ovarian/fallopian tube/primary peritoneal cancer. VELIA examined veliparib added to CP followed by veliparib maintenance compared to placebo added to CP followed by placebo maintenance. This analysis compared QA progression-free survival among patients enrolled in VELIA. Methods: Patient-centered outcomes were assessed in 344 Veliparib+ CP and 351 CP alone subjects. Progression-free survival (PFS) time was partitioned into two health states: time with toxicity (Tox) and time without Tox. Tox included three clinically meaningful adverse events (AEs) including nausea, vomiting and fatigue. QA-PFS was assessed for duration of good quality of life, incorporating PFS and health states. Q-TWiST (QA time without disease symptoms or treatment Tox) was calculated as utility-weighted sums of mean health state durations. Sensitivity analyses were conducted utilizing Grade 2+ or Grade 3+ AEs. Similar analyses were conducted on HRD and BRCA-deficient subgroups. Results: A significant difference in mean QA-PFS was seen in favor of Vel throughout compared to CP alone (19.5 months vs 16.5 months; 95% CI 1.42, 4.61; p<0.0001). Mean Q-TWiST was longer for patients in Vel throughout arm compared to CP alone (20.82 months vs 18.06 months; 95% CI 1.09, 4.47; p<0.001). Similar differences in mean Q-TWiST were observed for sensitivity and subgroup analyses. Conclusion: Compared to CP alone, Veliparib added to CP and continued as maintenance had significant patient-centered benefits in terms of QA-PFS and on-treatment Q-TWiST.